Electrical characterization of chitosan film for mercury ion detection by using four-point probe method - Radzali, Rashidah; Osman, Nurul Huda; Yap, Wing Fen; Liew, Josephine Ying Chyi (Asian Online Journals, 2016)
This paper reports the results of electrical characterization of chitosan film for mercury ion detection. The electrical resistivity of the film with different concentration, temperature and contact time with mercury solution was studied. This parameters have been measured with four-point probe method by the measurement of current (nA) and voltage (mV). The experimental results show that the variation of the concentration, mercury solution temperature and contact time between chitosan film and the mercury solution affected the resistivity of the chitosan film. This study has shown the capability of chitosan to bind mercury ions by chelation as one of its main properties and the present study will be a good base for further development of lab-on-chip sensor for heavy metal detection.